Implementation of Natural Language Processing On Chatbot for Tourist Information Services (Case Study: Serang City) - Wira Hadinata; Lilis Stianingsih (Sean Institute, 2025)
This research aims to develop and implement a chatbot system based on Natural Language Processing (NLP) that can provide tourist information services in Serang City. With the increasing need for fast and accurate information in the digital era, it is hoped that chatbots can be an effective solution to help tourists obtain information regarding tourist attractions, accommodation and activities in Serang City. The methods used in this research include data collection through interviews and surveys, as well as developing an NLP model using natural language processing techniques to understand and respond to user questions. The results of this research show that the chatbot developed is able to provide relevant and satisfying answers to users. In addition, feedback from users shows that this chatbot improves tourists' experience in exploring Serang City. It is hoped that this research can become a reference for the development of technology-based tourism information systems in other areas.